THEORETICAL AND EXPERIMENTAL EVALUATION OF A MODIFIED COMPOUND PARABOLIC CONCENTRATING SOLAR COLLECTOR USING OIL-BASED NANOFLUIDS - AKHTER, JAVED (2020)
Thermal oils, generally used as heat transfer fluids (HTFs) in the medium temperature compound parabolic concentrating (CPC) collectors, bear weak thermal properties that negatively affect their performance thereby creating a major hurdle in the successful application at industrial scale